PENGARUH MEDIA MASSA PADA PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA - Sunarto, Sunarto (JURNAL ILMU SOSIAL, 2007)
Mass media have strategic role to eliminate household violence through its support to goverment policies that prevent and service victims of the violence. The media's functions can be done through disseminating information intensively taht defent women's interests as victim the violence. This situation can be actualiized when the gender structure of the media has been engendered. Unfortunately the situation can not be done easily since capitalism and patriarchy mastering the media structure. Engendering the gender media structure can be done through engendering rules and resources of media's agents that gender sensitive. Since our gender social structure has had been engendering it is necessary to reinforce and maintain the structure to support media's gender structure.